PENGUATAN PENEGAKAN HUKUM HAK KEKAYAAN INTELEKTUAL: Studi Kritis terhadap Peran Pendidikan Kewarganegaraan - Tusriyanto, - (2011)
The law enforcement on Intellectual Property Rights (IPR) has not been successful due to the domination of repressive efforts rather than the pre-emptive and preventive ones. This research discusses about the role of CE in the strengthening of the law enforcement of IPR. The objectives of this research are to investigate: (1) the effectiveness of the law enforcement on IPR, (2) the constraints to the law enforcement on IPR, (3) the efforts to deal with the constraints; (4) the CE model of IPR National Team, (5) the weaknesses of the CE model of IPR National Team; (6) the efforts to deal with the weaknesses of the CE model of IPR National Team; and (7) the role of CE in the strengthening of the law enforcement of IPR. The law enforcement is influenced by many factors. According to the theory claimed by Talcott Parsons, the working system of a law is influenced by other social systems. The law enforcement shall be throughly viewed from such aspects as substance, structure, and culture of the community. The legal culture of the community which is different from the culture of IPR encourages the importance of an educational approach. CE is one of the approaches in the strengthening of the law enforcement of IPR. The research used a qualitative method. The samples of the research were gathered by using purposive sampling and snowball sampling techniques. Its data were gathered through library research, in-depth interview, observation, and focus group discussion. They were then analyzed by using interactive and bottom up models of analysis. The results of the research show that: (1) The law enforcement on IPR has not been effective; (2) The law enforcement on IPR have still undergone substantial, structural, and cultural constraints; (3) the constraints to the law enforcement on IPR can be overcome by clarifying the prevailing regulations, improving the apparatuses' professionalism, and creating and developing the awareness on IPR; (4) The CE model of IPR National Team includes the preemptive and preventive activities; (5) The weaknesses of the CE model of IPR National Team are related to the substance, target, and methods; (6) the CE model of IPR National Team shall be improved by strengthening the substance, target and methods; (7) CE can become an educational medium for awareness on IPR through the internalization of the values contained in CE and IPR such as honesty, respect, responsibility, justice, equality and democracy. Keywords: Law Enforcement, IPR, CE. Penegakan hukum HKI belum berhasil disebabkan dominasi upaya represif daripada pre-emtif, dan preventif. Penelitian ini membahas tentang peran PKn dalam memperkuat penegakan hukum HKI. Penelitian ini bertujuan mengetahui: (1) efektivitas penegakan hukum HKI; (2) Kendala-kendalanya; (3) Upaya-upaya mengatasi kendalanya; (4) Program PKn Timnas HKI; (5) Kelemahan program PKn Timnas HKI; (6) Upaya mengatasi kelemahan kegiatan PKn Timnas HKI; (7) Peran PKn untuk memperkuat penegakan hukum HKI. Penegakan hukum dipengaruhi oleh berbagai faktor. Menurut Teori Talcott Parsons, sistem bekerjanya hukum dipengaruhi oleh sistem sosial yang lain. Penegakan hukum perlu dilihat secara menyeluruh dari aspek substansi, struktur, maupun kultur masyarakat. Budaya hukum masyarakat yang berbeda dengan budaya HKI menyebabkan pentingnya pendekatan pendidikan. PKn merupakan salah satu pendekatan untuk memperkuat penegakan hukum HKI. Penelitian ini menggunakan metode kualitatif. Metode sampling (subyek penelitian) yang digunakan adalah purposive sampling dan snowball sampling. Teknik pengumpulan data dilakukan dengan studi pustaka, observasi, wawancara, dan focus group discussion (FGD). Analisis data menggunakan interactive model dan bottom up model. Hasil penelitian menunjukkan bahwa: (1) Penegakan hukum HKI belum efektif; (2) Penegakan hukum HKI masih mengalami kendala substansial, struktural dan kultural; (3) Kendala penegakan hukum HKI dapat diatasi dengan memperjelas peraturan, peningkatan profesionalisme aparat, dan membangun kesadaran HKI; (4) Program PKn Timnas HKI berupa kegiatan pre-emtif dan preventif; (5) Kelemahan program PKn Timnas HKI terletak pada aspek substansi, sasaran dan metode; (6) Program PKn Timnas HKI perlu diperbaiki dengan penguatan substansi, sasaran, dan metode; (7) PKn dapat menjadi wahana pendidikan kesadaran HKI melalui internalisasi nilai-nilai yang terkandung dalam PKn dan HKI berupa kejujuran, penghormatan, penghargaan, tanggung jawab, keadilan, kesetaraan dan demokrasi. Kata kunci: Penegakan Hukum, HKI, PKn